2002
DOI: 10.1046/j.1523-1747.2002.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Murine Melanocyte Precursors Induced by 1,25-Dihydroxyvitamin D3 Is Associated with the Stimulation of Endothelin B Receptor Expression

Abstract: The effects of 1,25-dihydroxyvitamin D3 on the differentiation of immature melanocyte precursors were studied. The NCC-/melb4 cell line is an immature melanocyte cell line established from mouse neural crest cells. 1,25-Dihydroxyvitamin D3 inhibited the growth of NCC-/melb4 cells at concentrations higher than 10(-8) m. That growth inhibition was accompanied by the induction of tyrosinase and a change in L-3,4-dihydroxyphenylalanine reactivity from negative to positive. Electron microscopy demonstrated that mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 42 publications
2
58
0
Order By: Relevance
“…Second, vitamin D compounds are known to influence maturation, differentiation, proliferation, migration, survival and melanin production of melanocytes [8,44,45,46]. In vitiliginous skin, calcium levels are significantly lower, and it is suggested that melanocyte response to melanogenic stimuli is modulated by calcium-dependent regulatory enzymes or transcription factors [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Second, vitamin D compounds are known to influence maturation, differentiation, proliferation, migration, survival and melanin production of melanocytes [8,44,45,46]. In vitiliginous skin, calcium levels are significantly lower, and it is suggested that melanocyte response to melanogenic stimuli is modulated by calcium-dependent regulatory enzymes or transcription factors [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, vitamin D has also been shown to have protective effects against melanocyte apoptosis [25,26]. It exerts these effects via interaction with the nuclear vitamin D receptor (VDR) on melanocytes [27][28][29]. Our patient experienced only minimal improvement with administration of topical and systemic vitamin D supplementation, suggesting that dasatinib therapy was the main driver of his pigment loss.…”
Section: Discussionmentioning
confidence: 87%
“…Tumours in this group also include neuroblastoma, Wilm's tumour, Ewing sarcoma and primitive neuroectodermal tumour. Elevated urinary vanillymandelic acid and the ability to differentiate primitive neural crest cells to neuroblastic and melanocytic lineages provide additional evidence (29)(30)(31)(32). Increased alpha-fetoprotein levels and positive staining for the c-myc antigen, characteristic of other neural crest tumours, has also been described (5,27,29,33,34).…”
Section: Discussion and Literature Reviewmentioning
confidence: 97%